LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT DALAM INDUSTRI SEPEDA MOTOR (KAJIAN PUTUSAN MAHKAMAH AGUNG NOMOR 217 K/PDT.SUS-KPPU/2019) - Hartanto Hartanto; Gilang Yudha Wirawan (Faculty of Law, Maranatha Christian University, 2021)
Business competition is an economic activity that runs in line with technological and industrial advances. With the existence of business competition, the Business Competition Supervisory Commission in Indonesia was formed which aims to supervise and protect business competition. This research will discuss the impact and legal consequences of the KPPU decision to the Supreme Court decision which still considers and uses circumstantial evidence and testimony based on hearing from other people. Based on the description above, the writer chooses the research title